A SYNTACTICAL ANALYSIS IN NON-STANDARD ENGLISH WORD OF MAC MILLER SONG LYRICS - Joko Wibowo (English Language Teaching Journal, 2022)
Every human being has at least one language, both spoken and written. The language contains basic or certain rules that form, combine, and express meaning that changes because words in language are combined differently through combinations in syntactic studies so that language has an important role in human life as a means of communication.This is actually the realization of the written examples.The Purpose of this research was to find out the non-standard and standard English words and to find out the tree structure in the Mac Miller song lyrics.Then, the writer choosessongs to analyze because studying songs does not just analyze the metaphorslanguage, word meaning and language style, but also analyze how non-standard English words can be used as standard English words by converting them with several tools such as phonological processes and basic grammar which in the song the English standard has been found the writer analyzessentence structureused in one of the lyrics to a song from Mac Miller's album entitled "Circles".In analyzing the data, the writer uses several appropriate theories with a subject for analyze sentences into each sentence content. This thesis uses a qualitative descriptive method. Steps in taking and the data collection are listening songs on the album "Circles" by Mac Miller, searching the lyrics of the internet, copying the lyrics of the songs to be analyzed, reading and identifying the non-standard English word and converted into standard English word using instrument for standardizing English words and the last make tree structure from the sentence or phrase. Moreover, the result after analyzing the data, the writer finally found fifteen rules in sentence structure and found thirty non-standard English word sentences in the lyrics of the song. Considering the importance of understanding sentence structure, especially in the study of syntax, the writer makes some suggestions, for students from English Department, other researcher who will conduct studies related to topics and the writer hopes that this thesis can be used as a reference or compare how non-standard English with their daily non-standard language and for those who are interested in studying syntax studies. Keywords: Syntactical Analysis, Non- Standard English Words, Mac Miller, and Song Lyric